Psychometric properties of a patient‐reported outcome set in acute stroke patients - Rebecca Philipp; Lisa Lebherz; Götz Thomalla; Martin Härter; Hannes Appelbohm; Marc Frese; Levente Kriston (Brain and Behavior, 2021)
Abstract Objectives Impairments after stroke may affect multiple domains of health‐related quality of life (HRQoL). Patient‐reported outcome measures (PROMs) have proven valuable in measuring patients’ well‐being. We examine the psychometric properties of a standard set of PROMs assessing global health, anxiety, and depression, and functioning in a German health care setting. Method We included inpatients at the Department of Neurology at the University Medical Center Hamburg‐Eppendorf, diagnosed with stroke. Following the stroke‐specific standard set of the International Consortium for Health Outcome Measurement, we collected demographic and clinical information at baseline, and PROMs for global health (PROMIS‐10), three items for self‐reported functioning, anxiety, and depression (PHQ‐4) at 90 days follow‐up. We calculated confirmatory factor analyses to test factorial validity and correlation analyses to test construct validity. We further conducted item and reliability analyses. Results In a sample of 487 patients (mean age, SD: 71.1, 12.6; 47% female) with mild and moderate symptoms, model fit for the PROMIS‐10 was acceptable for the two‐factor and single‐factor models. Factor loadings ranged from 0.52 to 0.94. The postulated single‐factor model for functioning was saturated with zero degrees of freedom. Factor loadings ranged from 0.90 to 0.96. For the PHQ‐4, the two‐factor model showed excellent model fit. Factor loadings ranged from 0.78 to 0.87. Internal consistency was acceptable to good. Construct validity was generally confirmed. Conclusions The PROMIS‐10 is a valid and reliable instrument to measure HRQoL among German stroke patients. While the PHQ‐4 was confirmed as a screening measure for mental disorders, further research is needed on items assessing self‐reported functioning. Results are limited to patients showing minimal functional deficits.